Literature Review: Regulations and Considerations - Yaiche, Ouassila (Al-Adab Journal, 2020)
This paper aims to highlight the importance of conducting a literature review to explore previous findings related to the topic of a research and acquaint the researcherswith the latest developments in that particular field. It also serves to assess the drawbacks of previous studies, which enables researchers to adopt different approaches or procedures to ensure that research value, originality and important contribution to the field are achieved. To attain these standards, the literature review must be adhere to certain regulations and take some considerations into account. This paper presents the concept of literature review, particularly the regulations that guide its writing and the considerations required when selecting, summarizing, classifying, presenting and synthesising previous studies.